Model-Based Bias Controller for a Mach-Zehnder Intensity Modulator - Svarny, Jiri; Chladek, Svatoslav (Journal of lightwave technology, 2022)
A new dither technique is presented to control the bias voltage of an intensity modulator of the Mach-Zehnder type to maintain the quadrature operating point. This method is based on the direct calculation of the operating point deviation. The calculation uses an exact mathematical model of the modulator. The data used for calculating the deviation value are obtained from an analysis based on a fast Fourier transform with a properly set level of vector averaging. Unlike other solutions, the proposed feedback system does not use an approach with a proportional-integral or proportional-integral-derivative controller. Moreover, the presented stabilization method is robust and invariant regarding changes in the input optical power of the modulator and immune to prospective fluctuations of most of the feedback loop parameters. With the proposed approach in its present form, a 3-hour stability of ±0.08° is achieved. This value reflects the limitations of the equipment used. Even better results can be expected using more powerful hardware.